2013
DOI: 10.1155/2013/749495
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine Banxiaxiexin Decoction Treating Diabetic Gastroparesis: A Systematic Review of Randomized Controlled Trials

Abstract: Objective. To assess the current clinical evidence of Banxiaxiexin decoction for diabetic gastroparesis (DGP). Methods. Electronic databases were searched until December 2012. No language limitations were applied. We included RCTs using Banxiaxiexin decoction/modified Banxiaxiexin decoction for DGP. No restriction for the control group except acupuncture. Applying clinical effective rate as the main outcome index. Data extraction, analyses and quality assessment were conducted according to the Cochrane review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…In the past decades, herb pair has been highly valued as the smallest compatibility units in TCM formula [ 51 ]. HL-BX became a classic herb pair in the treatment of DGP.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, herb pair has been highly valued as the smallest compatibility units in TCM formula [ 51 ]. HL-BX became a classic herb pair in the treatment of DGP.…”
Section: Discussionmentioning
confidence: 99%
“…Banxia Xiexin decoction (BXD) consists of seven herbs (Table 2) and is an effective Chinese medicine prescribed for treatment of gastroenteritis, ulcerative colitis, vomiting, and diarrhea (Tian et al, 2013; Wang X. et al, 2014; Wang Y. et al, 2014). Wang Y. et al (2014) successfully used a validated UPLC–MS/MS method to accurately quantitate 18 bioactive compounds in BXD, including flavonoids, alkaloids, and saponins.…”
Section: Herbal Medicines For Treatment and Prevention Of Cpt-11-indumentioning
confidence: 99%
“…A recent review of the literature indicated that only small studies have so far been published, from which no definite efficacy or safety conclusions could be made. 56 …”
Section: Banxiaxiexin Decoctionmentioning
confidence: 99%